Penerapan Aplikasi E-Court di Pengadilan Agama Sungguminasa Kelas I B - Ali, Nur Atira; Bakry, Muammar; R., Abd. Rahman (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2022)
This study aims to determine the application of the e-court application at the Sungguminasa Religious Court Class I B. This research is a qualitative research with a juridical approach. The main data sources in this study are interviews with judges, clerks, and advocates who know clearly about the application of e-court applications at the Sungguminasa Religious Court Class IB. Furthermore, data collection in this study used observation, interviews and documentation. Meanwhile, data processing and analysis techniques were carried out through three stages, namely: data reduction, data presentation and conclusion drawing. The results of the study show that the application of e-court applications has not been maximized. This can be seen from the users of the e-court application only from registered users (advocates) and none of them have been used by other users (non advocates), this is due to the lack of Human Resources (HR) in the field of Information Technology (IT). Therefore, the benefits of the e-court application can only be felt by some groups, namely for people who are technology literate and who are always active in getting information about e-court applications. Keywords: Application, E-court Application, Information Technology